2019
DOI: 10.1080/17482631.2019.1656790
|View full text |Cite
|
Sign up to set email alerts
|

Life strategies of people with deafblindness due to Usher syndrome type 2a - a qualitative study

Abstract: Purpose: To explore life strategies in people with Usher syndrome type 2a. Background: There are no studies on life strategies in people with Usher syndrome. People with deafblindness are often described in terms of poor health and low quality of life, or as being vulnerable. From a clinical point of view, it is of importance to balance this picture, with an increased knowledge of life strategies. Methods: The study had a qualitative explorative design. Fourteen people aged 20-64 years (4 women, 10 men) with U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 28 publications
3
28
0
3
Order By: Relevance
“…A review of existing research on determinants that are associated with the quality of life of people with deafblindness due to Usher syndrome has found that the adjustment of living habits, maintaining hope for the future and a belief in one's own capacity to accomplish goals are important in maintaining a good quality of life (Arcous et al, 2019). Being an active agent in one's own life has also been identified when having to adopt to new situations due to a USH, which is a disease with a progressive course (Ehn et al, 2019). Furthermore, social participation and inclusion have been reported as having a positive impact on the health-related quality of life for persons with deafblindness (Dean et al, 2017).…”
Section: Deafblindnessmentioning
confidence: 99%
“…A review of existing research on determinants that are associated with the quality of life of people with deafblindness due to Usher syndrome has found that the adjustment of living habits, maintaining hope for the future and a belief in one's own capacity to accomplish goals are important in maintaining a good quality of life (Arcous et al, 2019). Being an active agent in one's own life has also been identified when having to adopt to new situations due to a USH, which is a disease with a progressive course (Ehn et al, 2019). Furthermore, social participation and inclusion have been reported as having a positive impact on the health-related quality of life for persons with deafblindness (Dean et al, 2017).…”
Section: Deafblindnessmentioning
confidence: 99%
“…Social support has been described as a variable that affects the psychological health for persons with USH positively ( Dean et al, 2017 ). To have strategies to concur difficulties when they occur ( Ehn et al, 2019 ) has also been described as positive as well as remaining active through work ( Ehn et al, 2016 , 2018 ) or by other engagements ( Ehn et al, 2019 ). Still, variables affecting the health of people with USH need to be studied from a life course, bio-psychosocial perspective to reveal possible interaction effects and consequences ( Arcous et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…If unknown, then support and rehabilitation efforts might have limited effects. People with USH also report, spending much effort in explaining their life situation to professionals and others ( Ehn et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations